2014
DOI: 10.1037/a0037222
|View full text |Cite
|
Sign up to set email alerts
|

When do words hurt? A multiprocess view of the effects of verbalization on visual memory.

Abstract: Verbal overshadowing reflects the impairment in memory performance following verbalization of nonverbal stimuli. However, it is not clear whether the same mechanisms are responsible for verbal overshadowing effects observed with different stimuli and task demands. In the present article, we propose a multi-process view that reconciles the main theoretical explanations of verbal overshadowing deriving from the use of different paradigms. Within a single paradigm, we manipulated both the nature of verbalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
(156 reference statements)
0
13
0
1
Order By: Relevance
“…They showed that labeling can hamper visual LTM memory, consistent with a verbal overshadowing effect (Brandimonte, Hitch, & Bishop, 1992); however, this effect can be reversed if the visual context for the studied item (e.g. its color) is reinstated at test (Brandimonte, Schooler, & Gabbino, 1997), and the impairing effect depends on the match between the type of verbal description (one label vs. description of features) and the information required at test (global or featurebased) (Brown, Brandimonte, Wickham, Bosco, & Schooler, 2014). They have also shown that verbal descriptions may be beneficial when generated in the presence of the stimulus, but not during a retention interval (Nakabayashi, Mike, Brandimonte, & Lloyd-Jones, 2012).…”
Section: Dual-trace (Visual + Verbal)mentioning
confidence: 97%
“…They showed that labeling can hamper visual LTM memory, consistent with a verbal overshadowing effect (Brandimonte, Hitch, & Bishop, 1992); however, this effect can be reversed if the visual context for the studied item (e.g. its color) is reinstated at test (Brandimonte, Schooler, & Gabbino, 1997), and the impairing effect depends on the match between the type of verbal description (one label vs. description of features) and the information required at test (global or featurebased) (Brown, Brandimonte, Wickham, Bosco, & Schooler, 2014). They have also shown that verbal descriptions may be beneficial when generated in the presence of the stimulus, but not during a retention interval (Nakabayashi, Mike, Brandimonte, & Lloyd-Jones, 2012).…”
Section: Dual-trace (Visual + Verbal)mentioning
confidence: 97%
“…Both memory traces may be used for retrieval, and thus enhance retrieval performance. Such advantages have been repeatedly shown, for example, in verbal recall of single items (Paivio and Csapo, 1973 ), as well as for verbalizations in recognition of faces (Brown and Lloyd-Jones, 2005 , 2006 ), drawings (Brown et al, 2014 ), pictures of mushrooms (Melcher and Schooler, 2004 ), and dynamic scenes (Huff and Schwan, 2008 ).…”
Section: Introductionmentioning
confidence: 94%
“…First, the dynamometer is continuous and substantially more sensitive than existing measures. Second, the device can be used without significantly impairing task performance, and may help to mitigate verbal overshadowing effects (Brown et al, 2014;Creswell et al, 2016;Schooler & Engstler-Schooler, 1990). Third, when a traditional warmth measure is used, substantial data (up to 70% of trials, are unusable because participants often solve the problem too quickly.…”
Section: Discussionmentioning
confidence: 99%
“…The authors proposed that the feeling of hunger, like many other non-verbal experiences, is difficult to put into words. It is also known that verbalization can be disruptive to both task performance and subsequent memory (e.g., Schooler & Engstler-Schooler, 1990;Schooler, 2002Schooler, , 2011Brown et al, 2014). To solve this problem, the authors tested whether handgrip pressure over time-as measured by a dynamometer-could be used as a visceral, non-verbal alternative to the commonly used self-report measures of hunger.…”
Section: A Visceral Alternativementioning
confidence: 99%
See 1 more Smart Citation